2017
DOI: 10.1007/s00267-017-0970-9
|View full text |Cite|
|
Sign up to set email alerts
|

Impacts and Policy Implications of Metals Effluent Discharge into Rivers within Industrial Zones: A Sub-Saharan Perspective from Ethiopia

Abstract: Kombolcha, a city in Ethiopia, exemplifies the challenges and problems of the sub-Saharan countries where industrialization is growing fast but monitoring resources are poor and information on pollution unknown. This study monitored metals Cr, Cu, Zn, and Pb concentrations in five factories’ effluents, and in the effluent mixing zones of two rivers receiving discharges during the rainy seasons of 2013 and 2014. The results indicate that median concentrations of Cr in the tannery effluents and Zn in the steel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 41 publications
2
36
0
1
Order By: Relevance
“…Sampling of nutrients from factory emissions was done concurrently with that of the rivers. The factories show typical year‐round emissions (Zinabu, Kelderman, van der Kwast, & Irvine, ). River water samples were collected at the outlet of four sub‐catchments and two catchments (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Sampling of nutrients from factory emissions was done concurrently with that of the rivers. The factories show typical year‐round emissions (Zinabu, Kelderman, van der Kwast, & Irvine, ). River water samples were collected at the outlet of four sub‐catchments and two catchments (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…As an important type of environmental pollutant, toxic metals can enter water bodies through various natural or anthropogenic pathways and occur in the water phases, sediments, and organisms, and exhibit different environmental geochemical behaviors and biological toxic effects. Human activities, such as mining and disposal of waste water containing toxic metals and industrial metal chelates from tanneries, steel mills, etc., are the main sources of metals in water and sediments, which lead to a decline in water quality [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of Pb were highest in the downstream zone of the Leyole river, likely due to the tannery discharges (Zinabu et al, 2017a). Though the industrial sources in the upstream parts of the rivers were found low in Pb emissions (Zinabu et al, 2017a), the relatively high Pb accumulation in the riverbed sediments (Figure 3.4.) probably shows the incidence of Pb pollution from other source(s) such as vehicles that are washed beside the river (Karrari et al, 2012).…”
Section: Heavy Metals Quality Assessment In the Kombolcha Rivers And mentioning
confidence: 96%
“…Policies regarding water protection are, however, limited to regulation of pollutants emission into waters through a "polluter pays" principle to be implemented by regional and local water bureaus, rather than a country-wide approach for preventive management. The city of Kombolcha in north-central Ethiopia is a typical example of a conurbation with extensive pollution from industrial and municipal discharges, as well as agricultural intensification (Zinabu et al, 2017a). While it is visually apparent that some stretches of the rivers running…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation